Role of Low Dose Overnight Dexamethasone Supression Test (Lodst) in Management Protocol for Cushing’s Syndrome - Ahmed, Tofail; Mahtab, Hajera; Tofail, Tania; Morshed, Md. A. H. G.; Rahman, Fatema B.; Khan, Shahidul A. (Highlights on Medicine and Medical Research Vol. 4, 2021)
Introduction: Low dose overnight Dexamethasone Supression Test (LODST) is a diagnostic tool for spontaneous Cushing’s syndrome (CS). A LODST negative excludes CS. But there are 2 exceptions - testing during silent period of Cyclic Cushing’s disease (CD) or a false negative in early or mild CD by one mg dexamethasone. Methods: We analyzed age and sex data of 154 LOSDT to see there risk association for CS. Results: The detection rate of CS by LOSDT is 26% and with 95% CI of Cortisol (211.27 to 373.69 nmol/L). Among 154 cases, 45(29.2%) are in pediatric age and 109 (70.8%) are female. The CS group do not differ from the rest in their sex and age group distributions (sig.>.136) but their age of CS group is significantly more with a Mean Difference 2.46 - 13.31 years( sig. 005). Binary logistic regression equation documented CS population is significantly different (.000) and such deference is influence by their age (sig. .021) but not by sex or age group (sig, > .743). Therefore, age is an independent risk factor for CS. Conclusion: We opine to use LODST as first tool for CS. And LODST negative cases to be evaluated by newer imaging and biochemical tests. Positive only in imaging are to be managed according to guideline(s) for incidentoloma. Negative cases for both tools need to be enrolled in follow up protocols when age > 30 years or symptoms score suggest CD and rest are to be excluded. Analysis of cumulative diagnostic and outcome data will help us to formulate more cost-effective management policy for CS.